Coral health assessment in Malaysia: a case study of Pulau Anak Datai, Langkawi - Ismail, Mohamad Saupi; Ilias, Zaidnuddin; Ismail, Md. Nizam; Goeden, Gerald B.; Chee, Kong Yap; Al-Mutairi, Khalid Awadh; Al-Shami, Salman Abdo (Springer, 2022)
The coral health of Pulau Anak Datai (PAD), located off the northwest of Langkawi, Malaysia, was assessed using the Coral Health Index (CHI) method. Three ecological parameters, namely, benthic cover, fish biomass, and microbes (Vibrio) were determined at four sites around the island in 2019. In addition, community parameters such as coral mortality index, coral richness, relative abundance, diversity index, Evenness tests, and reef morphology were measured for each site. The results revealed that the benthic cover consists of less than 40% of scleractinian corals at all sites. A total of 25 genera of hard corals comprising of 11 families and 1 scleractinian Incertae sedis were observed, with the most dominant corals belong to the genera Porites, Favites, and Diploastrea. The average fish biomass of PAD was low (16.76 g/m2), with only 19 non-cryptic fish species observed. The abundance of Vibrio around the island was within the average range of 29.58 cfu/ml. Based on the benthos, fish, and Vibrio values, the Coral Health Index (CHI) of PAD was classified on the low side of the fair status. All sites tended toward high values of the mortality index (MI > 0.33). Reef morphology was strongly influenced by stress-tolerant corals, dominated by massive and sub-massive corals. The data presented here suggested that the reefs of PAD could be rated as stressed and becoming unhealthy and disturbed. However, in view of the rarity of coral reef ecosystems in the Straits of Malacca, this island deserves increased attention for conservation planning and coral reef protection.